High-level Executable Specification of the Universal Plug and Play Architecture - Glässer, Uwe; Gurevich, Yuri; Veanes, Margus (HICSS 2002, 2002)
Recently, Microsoft took a lead in the development of a standard for peer-to-peer network connectivity of various intelligent appliances, wireless devices and PCs. It is called the Universal Plug and Play Device Architecture (UPnP). We construct a high-level Abstract State Machine (ASM) model for UPnP using AsmL. AsmL is an advanced ASM-based executable specification language that has been developed at Microsoft Research. It provides a modern specification environment that is object-oriented and component-based. AsmL is integrated into Microsoft Visual Studio, Word and COM.